Rol de las proteínas hsp60 y de los receptores TLRs en la menopausia): Kim YS, Koh JM, Lee YS, Kim BJ, Lee SH, Lee KU, Kim GS. Bone 2009, 45(1):68-76. - del Valle Pérez, Adriana (Actualizaciones en Osteología, 2024)
-